2015
DOI: 10.1097/rct.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Liver Perfusion by IntraVoxel Incoherent Motion (IVIM) Magnetic Resonance–Diffusion-Weighted Imaging

Abstract: This study verifies Le Bihan's theory, confirming that in the liver, D* is influenced by perfusional changes related to portal venous flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
1
8
2
Order By: Relevance
“…The meal challenge induced an expected large increase in portal vein flow in healthy volunteers, as seen in previous MRI studies, [25][26][27][28] which resulted in an increase in liver T * 2 approaching significance as oxygen consumption decreased. 29 T * 2 of the liver is influenced by both iron 30 and oxygen content, but iron content does not change in response to the meal and therefore any change in liver T * 2 can be attributed to changes in oxygenation of the liver tissue.…”
Section: Discussionsupporting
confidence: 59%
“…The meal challenge induced an expected large increase in portal vein flow in healthy volunteers, as seen in previous MRI studies, [25][26][27][28] which resulted in an increase in liver T * 2 approaching significance as oxygen consumption decreased. 29 T * 2 of the liver is influenced by both iron 30 and oxygen content, but iron content does not change in response to the meal and therefore any change in liver T * 2 can be attributed to changes in oxygenation of the liver tissue.…”
Section: Discussionsupporting
confidence: 59%
“…However, there were no significant changes in parameters related to perfusion, such as D * and PF, after food intake. Unlike our study, Regini et al reported that D * increased after food intake [8]. We supposed that two factors might contribute to the different results.…”
Section: Discussioncontrasting
confidence: 55%
“…Various fitting algorithms have been used to determine IVIM parameters, including asymptotic fitting (9)(10)(11)(12)(19)(20)(21)24,41,45,46,48,51,53), nonlinear least square (usually Levenberg-Marquardt) fitting (23,42,47,52,54,55), and Bayesian fitting (15,22,40,43,50). Current review cannot draw conclusion which one is better than others, nor can the mean values be compared (Figure 8).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
“…Accumulation of collagen deposits and activated stellate cells contribute to increased hepatic resistance to portal blood flow, development of portal hypertension, and reduced portal blood perfusion. The decrease of blood perfusion can arise from a number of concomitant alterations in the tissue microenvironment, including collagen deposition, fatty (9)(10)(11)15,23,24,42,43,45,46,(48)(49)(50)(51)(53)(54)(55), free-breathing (FB) (19)(20)(21)40,41,47), and breath-hold (BH) (44). Solid line represents the median value of each group.…”
Section: Ivim For Liver Fibrosis Evaluationmentioning
confidence: 99%